Determinants of obesity risk factors in pre-seniors and seniors in Central Java: 2023 survey analysis - Yayuk Fathonah; Titik Kuntari; Yaltafit Abror Jeem; Nur Aisyah Jamil (Institute of Computer Science (IOCS), 2026)
Background: Overweight and obesity are increasing globally and in Indonesia, particularly among pre-seniors and seniors. Age-related changes and behavioral factors heighten obesity risk. Data from the 2023 Indonesian Health Survey (SKI) show a high burden of obesity among older adults in Central Java. Objective: To identify determinants of overweight and obesity risk factors among pre-seniors and seniors in Central Java based on the 2023 SKI data. Methods: A cross-sectional study using secondary data from 23,602 respondents aged ≥45 years in Central Java. Nutritional status was assessed using Body Mass Index (BMI). Sociodemographic characteristics, consumption patterns, and physical activity were analyzed using chi-square tests and multivariate logistic regression to estimate Adjusted Odds Ratios (aOR). Results: 42.2% of respondents were overweight or obese. Risk factors included age ≥60 years (aOR=1.695), urban residence (aOR=1.349), and daily sweet beverage consumption (aOR=1.374). Protective factors included male sex (aOR=0.414), low education (aOR=0.628), marital status (married/widowed), and heavy physical activity (aOR=0.808). Moderate physical activity was not significant after adjustment. Conclusion: Obesity among pre-seniors and seniors in Central Java is influenced by demographic, social, and behavioral factors, indicating the need for tailored prevention strategies for older adults.